Analisis Penyaluran Kerja Perusahaan LPK Monas Edukasi Indonesia Kepada PT. Kyoraku Blowmolding Indonesia - Anzar Nurrafli; Enjang Suherman; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Currently, Job Training Institutions are often carried out intentionally to reduce training costs within the company with the protection and work conditions provided. The role of the Job Training Institution company as a facilitator of workforce distribution is crucial in connecting job seekers with various available job vacancies. The aim of this research is to examine the methods involved in hiring, choosing, and allocating employees from LPK Monas Edukasi to PT. Kyoraku Blowmolding.. Kyoraku Blowmolding. This study uses a Qualitative Descriptive methodology by conducting interviews, observations, and documentation on the research data. The results of this study are that the job distribution process carried out by LPK Monas Edukasi Indonesia is running quite well. LPK has tried to connect job seekers with companies, starting from recruitment, selection, to job placement. However, there are still obstacles such as the lack of administrative readiness of applicants and the gap between the expectations of workers and the reality in the company. The company has requirements in the form of documents for them to fulfill, and for the selection itself, several tests are carried out, namely academic tests and interview tests after passing a letter of agreement is made from the company as proof of being accepted to work at the company they are applying for.